Anomalous Channel Length Dependence of Hot-Carrier-Induced Saturation Drain Current Degradation in n-Type MOSFETs - 张春伟 刘斯扬 孙伟锋 周雷雷 张艺 苏巍 张爱军 刘玉伟 胡久利 何骁伟 (Chinese physics letters, 2015)
The dependencies of hot-carrier-induced degradations on the effective channel length Lch,eff are investigated for n-type metal-oxide-semiconductor field effect transistor （MOSFETs）. Our experiments find that, with decreasing Lch,eff, the saturation drain current （Iasat ） degradation is unexpectedly alleviated. The further study demonstrates that the anomalous Lch,eff dependence of Idsat degradation is induced by the increasing influence of the substrate current degradation on the lazar degradation with Lch,eff reducing.